O processo de inclusão na educação infantil: estudo de uma escola do município de Cachoeira do Sul/RS - Machado, Raíssa Anahy (2022)
The present study is linked to the Research Line Pedagogical Management and Educational Contexts, of the Graduate Program in Public Policies and Educational Management at the Federal University of Santa Maria - UFSM, and emerged from the experiences and observations made throughout academic life. and professional performance. In this way, the question that guided this research was: how are the pedagogical practices of teachers from a kindergarten school in the city of Cachoeira do Sul/RS organized to ensure the inclusion and learning of children who are the target audience of Special Education? In this perspective, the general objective was to investigate the pedagogical practices of teachers of an Early Childhood Education school in the city of Cachoeira do Sul/RS, with regard to the process of inclusion and learning of children who are the target audience of Special Education. The specific objectives were: a) To identify the conceptions of teachers and school management regarding the process of inclusion in early childhood education; b) Diagnose the challenges faced by teachers during the process of inclusion in Early Childhood Education classes; c) Analyze the organization of teachers' pedagogical plans and practices for inclusion; d) Analyze the actions developed by school management in order to contribute to the pedagogical practices of teachers; e) Produce a diagram of the flow of actions for the promotion of inclusive education. This research followed a qualitative approach, of the case study type, as it used a single school institution as a basis. Data collection was performed through a semi-structured narrative interview with eight subjects. Data analysis was developed in the Content Analysis proposal, organizing the most relevant aspects for the constitution of this research, from the content categorization.Thus, three categories emerged: “The process of inclusion in Early Childhood Education: conceptions of teachers and management team”; “'Pedagogical practices in Early Childhood Education: planning and methodological strategies”; “Challenges encountered by teachers and management team during the inclusion process”.The resulting product of this investigation took place through a diagramming of the flow of actions of a school for the promotion of Inclusive Education, designed and structured to serve as a model, covering the basic paths and pedagogical paths that a proposal of inclusive education needs in school.